Spin-dependent beating patterns in thermoelectric properties: Filtering the carriers of the heat flux in a Kondo adatom system - Seridonio, A. C. [UNESP]; Siqueira, E. C. [UNESP]; Franco, R.; Silva-Valencia, J.; Shelykh, I. A.; Figueira, M. S. (My University, 2014)
We theoretically investigate the thermoelectric properties of a spin-polarized two-dimensional electron gas hosting a Kondo adatom hybridized with a STM tip. Such a setup is treated within the single-impurity Anderson model in combination with the atomic approach for the Green's functions. Due to the spin dependence of the Fermi wave numbers, the electrical and thermal conductances together with thermopower and Lorenz number reveal beating patterns as a function of the STM tip position in the Kondo regime. In particular, by tuning the lateral displacement of the tip with respect to the adatom vicinity, the temperature, and the position of the adatom level, one can change the sign of the Seebeck coefficient through charge and spin. This opens a possibility of the microscopic control of the heat flux analogously to that established for the electrical current.